THE METABASIC ROCKS FROM AÇUNGUI SUPERGROUP, ARAÇAIBA TOPOGRAPHIC MAP, SOUTHEAST OF SÃO PAULO STATE - Godoy, Antonio Misson [UNESP]; Duarte, Nicolli Ochi [UNESP]; Vieira, Otávio Augusto Ruiz Paccola; de Godoy, Daniel Françoso [UNESP] (UNESP - Universidade Estadual Paulista, 2023)
The ortho-derived rocks of basic and ultrabasic composition of meso-to neoproterozoic age of the region of Araçaiba, southeast of the state of São Paulo, are constituted by amphibolites and metabasites are located in the portion northern of the Apiaí Terrain, associated with the rocks of the metavolcanic sedimentary sequences of the Açungui Supergroup, specifically in the rocks of the Água Clara Formation. The main mineral paragenesis consists igneous pseudomorph of piroxene ± labradorite, ferrohornblende-magnesiohornblende ± oligoclase / andesine, representing the progressive regional metamorphism M1 climax, from 579 °C to 606 °C in temperature and 6.6 kbar (± 0, 6), mid amphibolite facies; and of magnesiohornblende-actinolite ± albite, from M3 regional retrometamorphism, low to mid greenschist facies. Geochemical data classify the igneous protoliths as into sub-alkaline low-potassium Fe-tholeitic gabbro and monzogabbro and alkaline picrite with a tendency to komatiitic basalts. Geotectonic data, corroborated by the behavior of trace elements and REEs, indicate three main signatures for amphibolitic groups: basic tholeitic and komatiitic rocks associated with mid-ocean ridge (MORB), with possible crust interaction in subduction phase; ultrabasic alkaline ocean island rocks (OIA); and island arc tholeiitic basalts (IAT). Therefore, this magmatism is correlated to the initial stage of opening of the basin or to the beginning of closure, to the initial phase of tholeitic ocean floor nature, associated with ocean island alkaline basalts.
AS ROCHAS METABÁSICAS DO SUPERGRUPO AÇUNGUI, FOLHA TOPOGRÁFICA ARAÇAÍBA, SUDESTE DO ESTADO DE SÃO PAULO
Keywords: Açungui Supergroup; Geochemistry; Geology; Metabasic